The School Analyzed from its Bases: A Student Perspective. An Approximation towards Rigid and Anomic Educational Institutions (Revista Peruana de Investigación Educativa, 2010)
In this article we propose an analysis of the world of the students’ everyday life, to understand the impact of the mechanisms of the educational institution in the students’ interactions and its subsequent resignifications. This investigation was carried out in two schools located in the community of Huaycan, in Lima. We propose there are two types of educative institutions. On the one hand we have an anomic institution that loses disciplinary power over the students, due to the students’ strategies to make the school a fruitful place coherent with their ludic perspectives. On the other hand we have a rigid institution that will difficult students’ socialization due to its panoptic organization and traces of totalitarianism. Both cases demonstrate how students will adopt a series of strategies to deliver different intentions and emotions, opposed to the adult-centric ones. They would establish an everyday world of their own values, independent of the vertical scholarity that inhibits their ludic ambitions, in a context of poverty and domestic violence.
Keywords: school discipline; educational interaction process; student adjustment; juvenile delinquency; teacher authority